Comparison of ART and conventional techniques on clinical performance of glass-ionomer cement restorations in load bearing areas of permanent and primary dentitions: A systematic review. (November 2018) - Ruengrungsom, Chirayu; Palamara, Joseph E.A.; Burrow, Michael F.
Abstract: Objectives: To review the clinical performance of GIC restorations using calculated annual failure rates (AFRs) and qualitative descriptions based on conventional and ART techniques from two aspects: occlusal and approximal cavities in permanent or deciduous posterior teeth. Sources: Search strategies were undertaken of the PubMed database from January 1983 to March 2018. Additional articles were collected by hand searching. Study Selection: The following basic search terms, "(glass ionomer cement) and (clinical performance or survival or ART or atraumatic restorative or high viscosity)" with inclusion and exclusion criteria according to PRISMA flow diagram were used. Data: A total of 904 articles were initially identified. Finally, 67 articles were included for quantitative and qualitative analysis after applying the inclusion and exclusion criteria. Assessment of risk of bias was performed for all included studies using ROBINS-I. Conclusions: For single-surface occlusal or multi-surface GIC restorations, the conventional technique showed better survival than ART technique regardless of dentition type (primary or permanent). When comparing the same treatment technique, AFRs of approximal or multi-surface GIC restorations were greater than those of single-surface (occlusal) restorations, irrespective of dentition type. RMGIC-conventional technique seems to be promising for restoring approximal cavities of primary teeth compared to other restorative materials. Clinical significance: The GIC-ART technique is an alternative option for single-surface (occlusal) restorations in permanent and primary teeth. However, the application of the GIC-ART technique for load-bearing approximal restorations should be carefully considered before employing this option, especially in primary teeth.